D02 Novel associations between within-day energy balance (WDEB) and relative energy deficiency in sport (RED-S) in recreationally active women - Moore, Helen L.; Bowden Davies, Kelly A.; Joanisse, Sophie; Morse, Chris I.; Stebbings, Georgina K. (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Relative energy deficiency in sport (RED-S) is a syndrome whereby physiological process are downregulated to regain energy balance under conditions of low energy availability (LEA). There is a growing body of research investigating the diverse health and performance complications in relation to energy availability calculated over 24-h. However this may conceal energy deficient periods in the day, which could contribute to RED-S symptoms. There is a handful of research suggesting such periods of deficiency are associated with changes in body composition, and menstrual and endocrine dysfunction, however many RED-S symptoms are yet to be explored in this area. This study therefore aimed to explore within-day energy balance (WDEB) in relation to a variety of, yet to be investigated, RED-S consequences in recreationally active women. Following ethical approval from the Manchester Metropolitan University Ethics Committee, 16 women (age, 27 ± 6 years, stature, 1.67 ± 0.05 m, and mass, 63.5 ± 8.2 kg) engaging in 4-6-h per week moderate-vigorous physical activity were recruited via social media, word of mouth, and posters. Seven-day food and training diaries alongside accelerometery and heart rate were used to estimate 24-h energy availability and hourly WDEB. The largest within-day energy surplus and deficit, the number of hours spent in a surplus and deficit, and the maximum number of consecutive hours in each, were calculated daily and averaged across the 7-days. Quantitative ultrasound of bone, haematocrit, haemoglobin, total cholesterol, maximum voluntary contraction of the knee during flexion and extension, V̇O2peak and lactate profile were all assessed. Gastrointestinal health was assessed via questionnaire. Correlational analysis between WDEB variables and RED-S symptoms was done accounting for 24-h energy availability. Of all 16 participants, 87.5% did not have adequate energy availability (<45 kcal∙kgFFM∙day-1); 12.5% had low energy availability (<30 kcal∙kgFFM∙day-1), and 75% had subclinical energy availability (30-45 kcal∙kgFFM∙day-1), typically associated with weight loss. Gastrointestinal dysfunction was negatively correlated with within-day energy surpluses (r13 = −0.479, P = 0.035) and positively correlated with within-day energy deficit variables (r13 = 0.499 to 0.534, P ≤ 0.029). These correlations were maintained after also accounting for anxiety. Haemoglobin levels were negatively correlated with within-day energy deficit variables (r13 = −0.477 to −0.490, P ≤ 0.036). Radius and tibia, T- and Z-scores were positively correlated with energy surplus values (r13 = 0.593 & 0.681, P = 0.004 & 0.013, respectively). To conclude, this was the first study to show WDEB to be associated with gastrointestinal, haematological, and bone health, illustrating that WDEB in relation to RED-S warrants further research as it may have health and performance implications that are overlooked when assessing LEA alone.